The Relationship between Smartphone Addiction, Academic Burnout and Academic Procrastination among University Students During Online Learning - Purnomo, Andreas Wisnu Adi; Wibowo, Ari Eko; Kurniawan, Kusnarto; Setyorini, Setyorini (Psikopedagogia, 2020)
The present study aimed to find out the simultaneous relationship among smartphone addiction, academic burnout, and procrastination among guidance and counseling department students of Semarang State University. This correlational study involved 75 students who were recruited using proportionate stratified sampling with a 10% margin of error. The data were analyzed using multiple correlation and bivariate formulas. The study revealed that 1) there is no significant relationship between smartphone addiction and procrastination, as indicated by a p-value of 0.449. In addition, it was also found that 2) there is no significant relationship between smartphone addiction and academic burnout (p-value = 0.255). However, the study found 3) a significant relationship between academic burnout and procrastination (p-value = 0.046). The fourth finding was that the R-value between smartphone addiction, academic burnout, and procrastination was 0.219 and sig. value of 0.171,Â  indicating a positive, insignificant simultaneous relationship between smartphone addiction, academic burnout, and procrastination among Guidance and Counseling Students of Semarang State University. The result of the study could be used as the basis to determine guidance and counseling services at the university level in order to minimize the problems related to smartphone addiction, academic burnout, and procrastination.